FOREST EDGE EFFECTS ON THE PHYTOSOCIOLOGICAL COMPOSITION OF AN ARAUCARIA FOREST FRAGMENT IN SOUTHERN BRAZIL - Scipioni, Marcelo Callegari; Lunardi Neto, Antônio; Siminski, Alexandre; dos Santos, Vanderlei (Floresta, 2018)
The Araucaria forests of Southern Brazil have been drastically reduced as a result of anthropic intervention and are currently found at different stages of succession. The objective of our study was to understand the influence of forest fragmentation on the phytosociological composition of its tree component. The composition of floristic groups of the tree component and their correlation with the edaphic and environmental variables in a fragment of the Araucaria Forest in the municipality of Curitibanos, state of Santa Catarina, Brazil was analyzed. A hundred and ten permanent continuous plots (10 m²) with forest edges of different origins and formation times were established for sampling. Trees with diameter ≥ 5 cm at breast height (DBH) were measured and identified. Using TWINSPAN, data were analyzed for species importance values (including indicator species) in the formation of floristic groups. Floristic similarities resulted in separating groups conditioned by the forest succession. The presence of the invasive species Pinus taeda L. and pioneer species at the forest expansion border contributed to the formation of a spatially cohesive group. The other areas did not show influence of edge effects, being in an initial secondary succession stage, dominated by Jacaranda puberula Cham. Low edaphic variation among the classes of lithosols in a flat relief had no influence on the formation of floristic groups.